Evaluación de los niveles de hormona antimülleriana sobre la dinámica folicular en vaquillas brahman - Alcívar Arteaga, Efrén Narcilo (2019)
Cattle are considered a fundamental pillar in livestock production, which requires establishing new assisted biotechnologies. The objective of this work was to determine the relationship between AMH levels and follicular dynamics in Brahman heifers of different ages. 20 heifers of 18-30 months of age were selected in a DCA factorial design (2x3) grouped into three blood ranges of AMH (100-200, 200-300 and 300-400 pg/ml; picograms/milliliter). In all the heifers the antral follicles, corpora lutea and size of ovaries were counted and measured. The data were submitted to ADEVA, Pearson correlations and regression; the means and the different interactions were compared with Tukey 5% (InfoStat 2017). A linear relationship was found between AMH levels and the number of total follicles and follicles of 2-4 mm (P<0,05) and R2 greater than 75%. A quadratic adjustment was obtained between the ages of the heifers and the total number of follicles, with a maximum value of 49 follicles when the heifers reached 23,5 months. It was evidenced that the number of total follicles and follicles of 2-4 mm was associated with the highest levels of AMH and heifers aged between 25-30 months (P<0,05); whereas the highest number of follicles of 4,1-7 mm was associated with AMH levels of 100-200 pg/ml in ages between 25-30 months. With these findings, it was concluded that at higher levels of AMH there is a larger follicular population.